2013
DOI: 10.1186/1471-2407-13-528
|View full text |Cite
|
Sign up to set email alerts
|

Pleural cancer mortality in Spain: time-trends and updating of predictions up to 2020

Abstract: BackgroundA total of 2,514,346 metric tons (Mt) of asbestos were imported into Spain from 1906 until the ban on asbestos in 2002. Our objective was to study pleural cancer mortality trends as an indicator of mesothelioma mortality and update mortality predictions for the periods 2011–2015 and 2016–2020 in Spain.MethodsLog-linear Poisson models were fitted to study the effect of age, period of death and birth cohort (APC) on mortality trends. Change points in cohort- and period-effect curvatures were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
(41 reference statements)
5
21
0
2
Order By: Relevance
“…Differences in the period of maximum burden of MPM cases are largely determined by past national consumption of asbestos and the implementation of bans of its usage [29]. This inference is also supported by asbestos consumption models, where the gap between the peak of asbestos use and that of MPM cases is estimated to be about 30 to 40 years [7,8,41,[43][44][45][46]. In our case, the Italian ban implemented in 1992 is probably starting just now to show its positive effects.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Differences in the period of maximum burden of MPM cases are largely determined by past national consumption of asbestos and the implementation of bans of its usage [29]. This inference is also supported by asbestos consumption models, where the gap between the peak of asbestos use and that of MPM cases is estimated to be about 30 to 40 years [7,8,41,[43][44][45][46]. In our case, the Italian ban implemented in 1992 is probably starting just now to show its positive effects.…”
Section: Discussionsupporting
confidence: 72%
“…Sweden is a notable exception, where the peak in MPM deaths was observed already in the 1990s [13], although a recent study seems to indicate a new increase in the number of deaths from mesothelioma after 2000 [37]. According to the most recent predictions, the number of MPM cases in Spain will increase at least until 2020 [41]. U.S. men have probably already reached the peak of MPM cases during the 2002-2007 period, although the MPM epidemic is predicted to last at least until 2042 [42].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical model most often used to make projections was the Poisson age-cohort, either classical3 19 23 28 29 31 32 34 36 38 40–42 or Bayesian 33 37. Others used log-linear or generalised additive models relating incidence of MM or mortality to past consumption of asbestos 20 21 22 24 26 27 32 35 39 44. Some authors found quite different predictions between the two approaches (eg, in France and UK), showing that the Poisson age-cohort model may overestimate future burden of MM compared with that obtained taking into account past use of asbestos 20 22.…”
Section: Discussionmentioning
confidence: 99%
“…31 We are currently witnessing a rise in number of these diseases, with the prediction that occupationally-related deaths due to pleural mesothelioma will continue in Spain until at least 2040. 32 Changes in the Spanish insurance system have been called for as a matter of urgency, and further research is required on OD recognition criteria. 33 Asbestos-related cancers were included in the OD list in 1978 in Spain, earlier than in France (1985), Italy (1994), and Belgium (1999).…”
Section: Discussionmentioning
confidence: 99%